2006
DOI: 10.2527/jas.2004-418
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cattle sex on carcass characteristics and longissimus muscle palatability1,2

Abstract: Two experiments were conducted to determine the effects of sex on carcass traits and cooked beef steak palatability. In Exp. 1, steers (n = 99), heifers (n = 51), and intravaginally spayed heifers (n = 46) were fed a high-energy diet for 161 d. No implants were administered, and heifers were not fed melengestrol acetate to suppress estrus. In Exp. 2, 60 steers and 60 intact heifers from the same ranch source used in Exp. 1 were fed in 2 locations (sites 1 and 2). All management factors were equal across experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
29
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 13 publications
9
29
1
8
Order By: Relevance
“…The CF steers and Ho bulls and both heifer breeds scored high for juiciness and Ho bulls scored high for beef flavour compared to 158 the other bulls. These observations agree with earlier results reporting better sensory scores for 159 steers than heifers and for heifers than bulls (Wulf et al 1996;Choat et al 2006;BureÅ¡ & 160 Bartoň 2012). Other results found, in contrast, no differences between steers and heifers or 161 between young bulls and heifers (Hoving-Bolink et al 1999) in terms of tenderness.…”
supporting
confidence: 93%
“…The CF steers and Ho bulls and both heifer breeds scored high for juiciness and Ho bulls scored high for beef flavour compared to 158 the other bulls. These observations agree with earlier results reporting better sensory scores for 159 steers than heifers and for heifers than bulls (Wulf et al 1996;Choat et al 2006;BureÅ¡ & 160 Bartoň 2012). Other results found, in contrast, no differences between steers and heifers or 161 between young bulls and heifers (Hoving-Bolink et al 1999) in terms of tenderness.…”
supporting
confidence: 93%
“…Differences between steers and heifers at Hamilton are, in some aspects, similar to those obtained by Choat et al (2006), where heifers in one experiment had a lower HSCW, a higher marbling score, a higher EMA and a lower yield, with no difference in rib fat. However, in the same paper, these authors reported that in another experiment they found that heifers had more rib fat, whereas there was no difference in HSCW or marble score.…”
Section: Effects Of Sexsupporting
confidence: 75%
“…This effect was still present after correcting for marbling score, despite evidence that this was likely to be due to differences in IMF (Drayer, 2003;Choat et al, 2006;Chriki et al, 2013). Furthermore, it was not affected by correction for any of the other covariates tested in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Many studies have shown increased marbling level, or intramuscular fat (IMF) is associated with greater tenderness, juiciness, flavour liking and overall liking (Thompson, 2004;Chriki et al, 2012). Therefore, the lower levels of IMF and lower marbling scores of bulls (Drayer, 2003;Choat et al, 2006;Chriki et al, 2013) would result in a lower eating quality. In addition to the sex effect on adiposity, the tenderness of meat from female cattle would be positively affected by the smaller fibre diameter and, in some cases, less collagen than meat from bulls (Boccard et al, 1979;Seideman et al, 1989;Chriki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%